Structural analysis of the housecleaning nucleoside triphosphate pyrophosphohydrolase MazG from Mycobacterium tuberculosis - Wang, Sen; Gao, Baocai; Chen, Anke; Zhang, Zhifei; Wang, Sheng; Lv, Liangdong; Zhao, Guoping; Li, Jixi (Frontiers in Microbiology, 2023)
The housecleaning enzyme of Mycobacterium tuberculosis (Mtb), MazG, is a nucleoside triphosphate pyrophosphohydrolase (NTP-PPase) and can hydrolyze all canonical or non-canonical NTPs into NMPs and pyrophosphate. The Mycobacterium tuberculosis MazG (Mtb-MazG) contributes to antibiotic resistance in response to oxidative or nitrosative stress under dormancy, making it a promising target for treating TB in latent infection patients. However, the structural basis of Mtb-MazG is not clear. Here we describe the crystal structure of Mtb-MazG (1-185) at 2.7 Å resolution, composed of two similar folded spherical domains in tandem. Unlike other all-α NTP pyrophosphatases, Mtb-MazG has an N-terminal extra region composed of three α-helices and five β-strands. The second domain is global, with five α-helices located in the N-terminal domain. Gel-filtration assay and SAXS analysis show that Mtb-MazG forms an enzyme-active dimer in solution. In addition, the metal ion Mg2+ is bound with four negative-charged residues Glu119, Glu122, Glu138, and Asp141. Different truncations and site-directed mutagenesis revealed that the full-length dimeric form and the metal ion Mg2+ are indispensable for the catalytic activity of Mtb-MazG. Thus, our work provides new insights into understanding the molecular basis of Mtb-MazG.